COVID‐19‐related discrimination, PTSD symptoms, and psychological distress in healthcare workers - Narita, Zui; Okubo, Ryo; Sasaki, Yohei; Takeda, Kazuyoshi; Takao, Masaki; Komaki, Hirofumi; Oi, Hideki; Mizoue, Tetsuya; Miyama, Takeshi; Kim, Yoshiharu (International journal of mental health nursing, 2023)
ABSTRACT To date, little effort has been made to examine if frontline workers who deal with COVID‐19 patients are more likely to experience discrimination than second‐line workers. Also, little information has appeared on how COVID‐19‐related discrimination affects PTSD symptoms in healthcare workers. We aimed to examine the association between COVID‐19‐related discrimination and frontline worker status. We further aimed to examine how COVID‐19‐related discrimination was associated with PTSD symptoms and psychological distress. We studied 647 healthcare workers. For the association between COVID‐19‐related discrimination and frontline worker status, we conducted multivariable logistic regression adjusting for age, sex and living alone. For the association of COVID‐19‐related discrimination with PTSD symptoms and psychological distress, we performed multivariable regression using hierarchical adjustments for age, sex, living alone, alcohol consumption, exercise and frontline worker status. Bias‐corrected and accelerated bootstrap confidence intervals (CIs) were used. A total of 136 individuals worked on the frontline and the largest group were nurses (n = 81, 59.6%). Frontline workers had increased odds of COVID‐19‐related discrimination compared with second‐line workers (odds ratio = 2.60, 95% CI = 1.37–4.96). COVID‐19‐related discrimination was associated with PTSD symptoms and psychological distress even at the highest level of adjustment (β = 0.67, 95% CI = 0.10–1.23; β = 2.43, 95% CI = 0.91–3.95, respectively). Frontline workers are more likely to experience COVID‐19‐related discrimination than second‐line workers. Such discrimination may result in PTSD symptoms and psychological distress. Interventions to prevent COVID‐19‐related discrimination against healthcare workers, for example anti‐discrimination campaigns, are important.